The Use of Multivariate Analysis in Development Theory: A Critique of the Approach Adopted by Adelman and Morris - Rayner, A. C. (Quarterly Journal of Economics, 1970)
Introduction, 639. — Factor analysis, 639. — Discriminant analysis, 644.